Social Science Approach Theory in Public Health - Maida, Maida (Journal Health of Indonesian, 2025)
Public health is influenced by various interrelated social factors. The social science approach to public health views disease not solely as a disease agent, but also as an imbalance between the host, the environment, and the agent itself. This article discusses various social science theories, such as John Gordon's epidemiological theory, Blum's theory, Maslow's behavioral theory, the Health Belief Model, and Lawrence Green's theory, which explain the factors shaping health behavior. In addition, sociological, anthropological, and demographic approaches are also discussed as a foundation for understanding the dynamics of public health. Qualitative and quantitative methods in the social sciences are explained as tools for analyzing health phenomena. This knowledge is essential for designing appropriate health programs, oriented towards the behavior, culture, and social conditions of the community.